Software evaluation using quantitative methods - Dasso, Aristides (2003)
Evaluation of software is an ever-present reality. We present an ongoing project that evaluates different families of software using the Logic Scoring of Preference method. This method is very briefly presented and also some of the ongoing evaluation work is explained